Brain morphometric changes in patients with fibromyalgia - Kudret Cem Karayol; Sunay Sibel Karayol (Journal of the Pakistan Medical Association, 2022)
The aim of this study was to determine whether there is a decrease or an increase in the volume of different regions of the brain by comparing brain morphometry ofpatients diagnosed with Fibromyalgia Syndrome and healthy control subjects. The study included 23 female patients who were diagnosed with fibromyalgia, and 18 females, age-matched healthy subjects. Structural Mitral Regurgitation data was processed using Surface-Based Morphometry (SBM) on the Freesurfer 6.0 programme (http://surfer.nmr.mgh.harvard.edu). As a result of the surface-based analyses, a statistically significant reduction was determined in the Fibromyalgia Syndrome patient group in some brain region. A statistically signficant increase was determined in the FMS patient group with respect to the left anterior occipital sulcus volume, left inferior temporal gyrus thickness and left anterior occipital sulcus area. The results of this study showed that FMS affected brain morphometry through the brain central pain mechanisms and the normal brain morphology was changed because of atrophy in some areas and hypertrophy in some areas. Keywords:Brain MRI, brain morphometry, fibromyalgia pain.